Effect of Constructivist Approach in Fostering Creativity of Primary School Children - Nayar, Rajendra Kumar; Senapaty, H.K. (JOURNAL OF INDIAN EDUCATION, 2011)
The purpose of this study was to determine the effect of constructivist approach on students’ creative ability. The study was a pre-test, post-test quasi experimental design and it was conducted in winter 2009 where 125 class-V students participated from two different English medium schools of Bhubaneswar city, Odisha. Learning in constructivist framework has been applied to experimental group and traditional teaching method followed by control group. The Creative Ability Test (CAT) used by the researcher to estimate the students’ creativity from both the groups. The hypothesis was tested at 0.05 level using t-tests. The result showed that learning in constructivist strategy improve students’ overall creative ability as well as other two different dimensions (Fluency, Flexibility) and no such difference found in case of Originality aspect of CAT. The researcher concluded that the constructivist approach is an effective strategy, which teachers need to incorporate in their teaching.